2011
DOI: 10.3390/en4020294
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on Gas Production Efficiency from Hydrate Deposits by Thermal Stimulation: Application to the Shenhu Area, South China Sea

Abstract: Gas hydrates have been attracted a great deal of attention because of their potential as an energy substitute and the climate implications. Drilling and sampling research on the hydrate deposit in the Shenhu Area on the northern continental slope of the Southern China Sea was a big breakthrough for hydrate investigation in China, but as a new potential energy source, how the gas can be effectively produced from hydrate deposits has become a hot research topic. Besides depressurization heat stimulation is regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Shenhu area is located in the Baiyun Sag, Pearl River Mouth Basin (PRMB) of the northern slope of the SCS (Figure 1). Geological, geophysical, geothermal, and geochemical investigations had suggested that Shenhu area is a beneficial district for the formation of NGH [18,24,26]. Gas hydrate samples were collected during a recent scientific expedition conducted by the China Geological Survey in this area in May 2007 and September 2015 [5,19,20,45].…”
Section: Numerical Models Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Shenhu area is located in the Baiyun Sag, Pearl River Mouth Basin (PRMB) of the northern slope of the SCS (Figure 1). Geological, geophysical, geothermal, and geochemical investigations had suggested that Shenhu area is a beneficial district for the formation of NGH [18,24,26]. Gas hydrate samples were collected during a recent scientific expedition conducted by the China Geological Survey in this area in May 2007 and September 2015 [5,19,20,45].…”
Section: Numerical Models Andmentioning
confidence: 99%
“…In order to seek the most economically and technically feasible method for gas production from the HBS, numerical simulation for its economic, convenient, and flexible response to complex geological problems was considered as the best way to achieve this objective. Based on the available geological data in Shenhu area of the SCS, Zhang et al [22] investigated the gas production performance by using two parallel horizontal wells to depressurize the HBS; Li et al [13,23] and Su et al [24][25][26] fully investigated the gas production potential and efficiency through depressurization and the combination of depressurization and 2 Geofluids thermal stimulation, respectively, employing both vertical and horizontal wells. Their results indicated low gas production rates and unsatisfied gas/water ratios because of low intrinsic permeability of the HBS and permeable overburden and underburden formations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the production simulation carried out by Moridis and Reagan only lasted about 1500 days in industry level [18]. Su et al [20] and Myshakin et al [21] employed the depressurization and thermal stimulation method to investigate vertical well hydrates dissociation, and found that the gas released rate was too small to reach industry-scale commercial production. Li et al attempted to produce gas by depressurization and the pull and hull method in horizontal well, but the results were not as satisfactory as expected [19,[22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…The application of the vertical well [28], the single horizontal well [25], and the dual horizontal well [15] technologies in the hydrate reservoir at the Shenhu Area were investigated. Evaluations of the gas production from hydrate reservoir by depressurization [29], thermal stimulation [30], the huff and puff method [26], and depressurization in conjunction with warm brine stimulation [31] were also studied. However, up to now, there was little literature about the evaluation of gas production from the hydrate reservoir in the Dongsha Area.…”
Section: Introductionmentioning
confidence: 99%